Republic of Armenia : Second Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2008)
The key findings of Republic of Armenia's Second Poverty Reduction Strategy Paper are reviewed. Macroeconomic and fiscal framework has been completely revised, taking into account the 2007 outcomes, tendencies developed during 2008, and challenges, particularly the projected increase of consumption prices and the GDP deflator. The structure of the economy has been reconsidered, targeting a larger share of industry and service sectors, mostly owing to the reduction in construction.